Design of the Texas Hepatocellular Carcinoma Consortium Cohort Study - Feng, Ziding; Marrero, Jorge A.; Khaderi, Saira; Singal, Amit G.; Kanwal, Fasiha; Loo, Nicole; Beretta, Laura; Ning, Jing; El-Serag, Hashem B. (The American journal of gastroenterology, 2019)
The Texas Hepatocellular Carcinoma Consortium cohort study investigates risk factors of hepatocellular carcinoma (HCC) and biomarkers for early HCC detection in patients with liver cirrhosis. Adult patients with liver cirrhosis are enrolled at 5 clinical centers from 3 cities in Texas, with a target of 5,000 patients. Clinical history, risk factor questionnaires, liver imaging, laboratory data, and blood samples were collected at enrollment and at each 6-month follow-up visit. The primary outcome was the development of HCC. Biomarkers were tested in banked blood samples using prospective specimen collection, retrospective blinded evaluation design. We describe study design, eligibility criteria, recruitment, study cores, and sample size and analysis considerations.